Back to the Future : Fiscal Rules for Regaining Sustainability - Cevik, Serhan (IMF Working Papers; Working Paper ;, 2019)
This paper assesses the cyclicality and sustainability of fiscal policy in Belize and applies a stochastic simulation model to determine the optimal set of fiscal rules. The empirical analysis shows that fiscal policy in Belize has been significantly procyclical and unsustainable much of the period since 1976. While the government's recent commitment to maintain a primary surplus of at least 2 percent of GDP until 2021 is supporting debt reduction, stochastic simulations indicate that further improvement in the primary balance is necessary to reliably bring the debt-to-GDP ratio to a sustainable path. Given Belize's history of large economic shocks, this paper proposes explicit fiscal rules designed for countercyclical policy and debt sustainability. It recommends integrating such rules into a well-designed fiscal responsibility law and establishing an independent fiscal council to improve accountability and transparency.